THE UNJUSTIFIABLE TARGETING OF HEALTHCARE IN PALESTINE: A VIOLATION OF HUMAN RIGHTS AND INTERNATIONAL LAW - Imtihani, Hajar; Nasser, Muhammad (The Islamic Education and Multiculturalism Foundation, 2024)
Introduction: The ongoing conflict in Palestine has severely impacted its healthcare system, with hospitals and medical personnel frequently targeted by Israeli forces. This paper examines the unjustifiable targeting of healthcare in Palestine, highlighting violations of human rights and international law. Objective: The study investigates the extent of these attacks, analyzes their legal implications, and proposes recommendations for protecting healthcare in conflict zones. Research problems: It addresses the legal issues of systematic and deliberate targeting of healthcare in Palestine, which constitutes a grave violation of human rights and international law, and seeks to shed light on the magnitude and consequences of this problem. Method: Using a multidimensional approach, this paper analyzes the legal and contextual issues surrounding the targeting of healthcare in Palestine. The analysis employs human rights theory to assess the impact of these attacks on fundamental rights. Results: Findings reveal a systematic pattern of attacks on healthcare facilities and personnel, leading to numerous casualties, infrastructure damage, and disruption of essential medical services. These attacks violate international humanitarian law, including the Geneva Conventions and the Rome Statute of the International Criminal Court. Conclusion: targeting of healthcare in Palestine is a serious violation of human rights and international law, calling for immediate action to protect healthcare and hold perpetrators accountable. Recommendations include strengthening international monitoring mechanisms, pursuing legal accountability through international courts, and increasing international pressure on Israel to respect its obligations under international law. Legal professionals must act decisively to address this crisis, aiming for a future where peace, justice, and the right to life and health are respected for all.